Spontaneous combustion of Canadian coals - K. K. Feng (Canadian Institute of Mining, Metallurgy and Petroleum, 1985)
"Spontaneous combustion has always been a problem in coal mines and is identified mainly with the mining of low-rank coals. The liability of coals to spontaneous heating is only one of the factors in determining whether spontaneous combustion will occur. However, knowledge of the relative oxidizability of the coal is a useful factor to take into consideration when selecting new coal seams and mining methods for future mine development.Four methods (static isothermal, ignitability, adiabatic and dynamic) have been used to compare the relative liability of Canadian coal to spontaneous combustion and to investigate the mechanism of spontaneous combustion of these coals. Among these f our methods, the static isothermal method is considered to be the best indicator of the susceptibility of various coals to spontaneous combustion. Western mountain coal adsorbs more oxygen and has a higher tendency to undergo spontaneous combustion than the Harbour seam coal of Nova Scotia. It has also been observed that a higher methane content in coal will indicate a lower liability to spontaneous heating."